Mobilizing political support proved critical to a successful switch from tOPV to bOPV in Kano, Nigeria 2016 - Bashir Abba; Sule Abdullahi; Samuel Bawa; Kabir Ibrahim Getso; Imam Wada Bello; Charles Korir; Audu Musa; Fiona Braka; Adamu Ningi; Peter Nsubuga; Richard Banda; Sisay G. Tegegne; et al. (BMC, 2018)
Abstract Background Kano is one of the high-risk states for polio transmission in Northern Nigeria. The state reported more cases of wild polioviruses (WPVs) than any other state in the country. The Nigeria Demographic and Health Survey of 2013 indicated that OPV3 coverage in the routine immunization (RI) programmewas 57.9%. Additionally, serial polio seroprevalence studies conducted from 2011 to 2015 in the eightmetropolitan LGAs indicated low immunity levels against all three polio serotypes in children below one year. Areas with sub-optimal RI coverage such as Kanothat fail to remove all tOPV during the tOPV-bOPV switchwill be at increased risk of VDPV2 circulation. Methods We assessed the impact of political leadership engagement in mobilizing other stakeholders on the outcomes of the bOPV-tOPV switch in Kano State from February to May 2016 using nationally-selected planning and outcome indicators. Results A total of 670 health facilities that provide RI services were assessed during the pre-switch activities. Health workers were aware of the switch exercise in 520 (95.1%) of the public health facilities assessed. It was found that health workers knew what to do should tOPV be found in any of the 521 (95.2%)public health facilities assessed. However, there was a wide disparity between the public and private health practitioners' knowledge on basic concepts of the switch. There was 100% withdrawal of tOPV from the state and the seven zonal cold stores. Unmarked tOPVwas found in the cold chain system in 2 (4.5%) LGAs. Only one health facility (0.8%) had tOPV in the cold chain. No tOPVwas identified outside the cold chain without the "Do not use" sticker in any of the health facilities. Conclusion The engagement of the political leadership to mobilize other key stakeholders facilitated successful implementation of the tOPV-bOPVswitch exercise and provided opportunity to strengthen partnerships with the private health sector in Kano State.